Transcatheter vs. surgical closure of patent ductus arteriosus: outcomes and cost analysis - Mulyadi M Djer; Mochammading Mochammading; Mardjanis Said (Indonesian Pediatric Society, 2013)
Background Patent ductus arterious (PDA) is a non-cyanoticcongenital heart disease (CHD) caused by the patency of thearterial duct after birth. For the last three decades, managementof PDA with transcatheter closure has been gaining popularity,including in developing countries. However its effectiveness interms of clinical outcomes and cost may vary among center andhas not been thoroughly evaluated yet in Indonesia.Objectives To compare the cost and clinical effectiveness of PDAclosure using transcatheter approach compared to surgical ligation.Methods We performed a retrospective review on patientsunderwent either transcatheter or surgical closure of PDA betweenJanuary 2000 and December 2006 in Cipto MangunkusumoHospital,Jakarta, Indonesia. Clinical outcomes as well as cost werecompared using the student T-test and Chi-square for numericaland categorical variables, respectivelyResults During the study period, 89 patients underwent transcatheterclosure using an AmplatzerÂ® device occluder (ADO) device and67 had surgical ligation. Successful PDA closure on first attemptwas achieved in 87 (96%) and 63 (94%) children who underwenttranscatheter and surgical closure, respectively (P = 1.000). Twochildren with unsuccessful transcatheter closure eventually hadtheir PDA closed by surgery, whereas one child with residual PDAafter surgical closure had his PDA closed by coil. No residual PDAwas found in the transcatheter closure group at one-week follow up.Duration of hospitalization was significantly less for patients havingtranscatheter closure compared to surgery [2.7 (SD 1.5) vs. 6.6 (SD1.5) days, P< 0.0001]. The cost for PDA closure with anAmplatzerÂ®device was more expensive than surgical ligation [Rp. 29,930,000 (SD57,200) vs. Rp. 12,205,000 (SD 89,300), P< 0.0001].Conclusion Transcatheter closure is equally effective as surgicalligation in closing the PDA. Less hospitalization is required withtranscatheter closure although the cost is higher than surgicalligation.